Mosquito prevention strategies can improve indoor heat stress in hot climates: a case of traditional Kenyan homes - Haiwei Li; Haimavati Raman; Bernard Abong’o; Teresa Bange; Yongling Zhao; Carol Brayne; Ronita Bardhan (Environmental Research: Health, 2025)
Global south faces detrimental impacts of climate change, particularly the escalation of extreme heat and the heightened prevalence of vector-borne diseases. This research investigates coupled health risks posed by indoor overheating and malaria transmission in Kisumu, Kenya, across 138 local residents and their thirty rural settlements in original building designs and modified forms. We evaluated a low-cost building design intervention—open eaves fitted with screens—through simulation-based analysis. This study introduces a coupled health risk assessment method, examining indoor heat stress and malaria transmission. It computes risk indices by evaluating exposure, vulnerability, and hazard, aligning with the IPCC’s risk assessment framework. The approach combines field measurement data, computational fluid dynamics simulations, and questionnaire surveys to analyze risk in homes, including factors related to the building designs and residents. Our findings highlight that traditional informal settlements with overcrowding, cooking activities, and poor ventilation largely increase indoor exposure and vulnerability. Over 10% of homes face extreme heat stress, with over 70% of indoor air exceeding 30 °C and 10% exceeding 35 °C. Houses with open eaves and windows reduce indoor overheating by 4%–15% in comparison to houses with closed roofs and windows. Roof-level ventilation via open eaves promotes airflow and reduces heat, while windows offer conflicting effects by mitigating heat but increasing mosquito entry. Adaptive strategies such as open eaves with screens can reduce the bi-fold risks of malaria and indoor overheating, but may increase the indoor air pollution if housing design features, such as window-opening schedules and door design are not considered from the hazard and exposure perspectives for the population. This study reveals the complex interplay of socioeconomic factors, adaption behaviors, and building design changes, offering insights for mitigating exposure and hazard in vulnerable Kenyan neighborhoods.